Proceedings 19th International Conference on Data Engineering (Cat. No.03CH37405)
DOI: 10.1109/icde.2003.1260881
|View full text |Cite
|
Sign up to set email alerts
|

DBProxy: a dynamic data cache for web applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
4

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 15 publications
0
66
0
4
Order By: Relevance
“…IBM DBCache [2,17], IBM DBProxy [3], and NEC CachePortal [16] all implement database query caching for web applications. Of these DBProxy uses a relation-based cache representation and sophisticated query processing at each proxy server, enabling a proxy to generate a response to an uncached query if the result can be composed from data retrieved by other cached queries.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…IBM DBCache [2,17], IBM DBProxy [3], and NEC CachePortal [16] all implement database query caching for web applications. Of these DBProxy uses a relation-based cache representation and sophisticated query processing at each proxy server, enabling a proxy to generate a response to an uncached query if the result can be composed from data retrieved by other cached queries.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, a number of systems have been proposed with a similar architecture for scaling the delivery of databasebacked dynamic content [3,2,17,22]. In each of these systems users interact with proxy servers that mimic a traditional three-tiered architecture (containing a web server to handle user requests, an application server to generate dynamic content, and a database server as a backend data repository).…”
Section: Introductionmentioning
confidence: 99%
“…Using the second assumption, their system solves strong consistency management of the servers. DBProxy [4] observed that most applications issue template-based queries and these queries have the same structure that contains different string or numeric constraints. AutoPart [14] deals with large scientific databases where the continuous insertions limit the application of indexes and materialized views.…”
Section: Automated Physical Design Solutionsmentioning
confidence: 99%
“…Goldstein and Larson [7] show the potential of materializing views within a relational system to dramatically improve performance of expensive queries. Both Amiri, et al [8] and Larson, Goldstein, and Zhou [9] addresses caching relational query results using materialized views. Amiri, et al perform caching in edge caches separate from the origin database which reduces load on the origin server, but maintaining consistency of cached results requires that the origin database propagate every update, delete, and insert operation to all caches, making it unsuitable for environments with high write throughput.…”
Section: Related Workmentioning
confidence: 99%